Propuesta de un sistema de información mediante arcgis 10.3 para los administrados del plan anual de evaluación y fiscalización ambiental, distrito de San Vicente de Cañete, 2018 - Sánchez Gaspar, Katherine Fiorella (2021)
Objective. Make the proposal of an information system through ArcGIS 10.3 for the administrations of the Annual Environmental Assessment and Enforcement Plan of the San Vicente de Cañete district, 2018. Methodology. Descriptive, non-experimental and crosssectional research, with a qualitative approach, for a sample of 101 municipal administrations. Those administered were identified and categori zed, the address of 48 of them did not appear in the document or did not correspond to that of the commercial establishment indicated by the municipality, being not located at the time the information was generated in the field, after Obtaining updated and georeferenced information from those administered in the field proceeded to the creation of a database in Excel, to finally generate a Geodatabase and load the geography information layer with ArcMap with the ArcGIS 10.3 software to obtain the mapping of PLANEFA 2018 administered. Results. For the 101 administered, it was registered by code, administered, trade name, Ruc, UTM coordinates, department, province, district, zone type, zone name, reference, operating license, civil defense certificate, fumigation certificate, environmental complaint, environmental monitoring, observations and photo. Of these, restaurants, chifas and chicken shops correspond to 41.58%, bakeries and pastry shops 1.98%, bars 2.97%, discos 2.97%, mechanical workshop 7.92%, lodgings 0.99% and wineries 41,58%. Of the total,only 52.48% of those administered is evidenced, and of the 23 administered supervised, 82.61% complied with environmental supervision. Developing the mapping of the district's PLANEFA administered universe with ArcGIS 10.3. Conclusions. The proposal of an Information System through ArcGIS 10.3, allows to improve environmental enforcement efficiently